PRODUÇÃO DE ENERGIA EÓLICA E ECONOMIA DE ENCLAVE: O caso do Parque de Paulino Neves (Maranhão) - MATA, Gabriel Reis da (2024)
This research seeks to analyze the possible impacts on the economy of the Maranhão municipality of Paulino Neves with the arrival of the wind farm in its territory, based on the hypothesis that this enterprise does not have sufficient potential to promote socioeconomic development in this location, functioning as an enclave economy. Therefore, we will investigate what enclaves are and how they are formed. To this end, the research is based on the ECLAC structuralist analysis of economic relations between economies that are at different productive stages. At this point, the level of development, underdevelopment and the main one, which is that of enclave economies, will also be determined. Further on, the market and production structure of the sector will be demonstrated, presenting its participation and importance for an economy. The first signs of technological dependence will be presented not only at the municipal level, but also at the national level, notes that will lead to the denial or affirmation of the initial hypothesis. Finally, the work covers the presentation of the municipality of Paulino Neves, showing its natural characteristics which, as in other parts of Brazil, are conducive to the arrival of these investments. Subsequently, an analysis of socioeconomic and fiscal indicators will be carried out, a key point in determining whether or not an enclave is a case.